PERSEPSI DAN ANALISIS KEBERLANJUTAN USAHA PERTANIAN TERPADU TERNAK SAPI DAN TANAMAN (Suatu Kasus Di Desa Cibodas, Kecamatan Pasirjambu, Kabupaten Bandung) - Nurhasanah, Salma; Rosmiati, Mia; Supriyadi, Aep (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
One area in West Java that has implemented an integrated farming system is Cibodas Village, Bandung Regency. Cibodas Village is the largest producer of cow's milk in Pasirjambu District. The initial problem faced by some farmers is the scarcity of forage feed and the high price of concentrate feed, besides that cow manure waste has not been managed properly, so it is feared that it will cause pollution to the environment. So, farmers and breeders of the village decided to do integrated farming since 2019 but until now only a few are interested and no evaluation has been carried out regarding the sustainability of integrated farming businesses in Cibodas Village. This study aims to assess the perception and sustainability status of integrated farming in Cibodas Village. This research used the RAP-CLS method (modified Rapfish-MDS) and the QSPM method (Quantitative Strategic Planning Matrix). Respondents were determined by purposive sampling. Based on the results of the study, the perception of farmers and breeders towards relative advantage is positive (43%), compatibility is positive (53%), complexity is positive (57%), triability is very positive (47%) and observability is positive (53%). The sustainability index in the ecological dimension is 44.06 or less sustainable, the economic dimension is 48.40 or less sustainable, the social dimension is 63.45 or moderately sustainable, and the technological dimension is 48.68 or less sustainable. The formulation of management strategies resulted in 8 alternative strategies. The conclusion of this study are that the perception of farmers and breeders is at a positive value, the sustainability status of integrated agricultural is at a fairly sustainable value with a average of sustainability index is 51.15 and prioritized development strategies are seeking direct cooperation between farmers and breeders with business actors in the food sector, increasing cooperation between extension workers and farmer groups in re-initiating integrated agriculture and preparing planting and livestock rearing plans in accordance with environmental conditions.